Drug complexation and physicochemical properties of vinylpyrrolidone-N, N′-dimethylacrylamide copolymers - De Queiroz, Alvaro A.A. (2004)
Solid dispersions of the nonsteriodal antiin-flammatory drug (NSAID) 2′,4′-difluoro-4-hydroxy-(1,1′-biphenyl)-3-carboxylic acid (DIF) with the water-soluble random copolymer poly(N-vinyl-2-pyrrolidone-co-N, N′-dimethylacrylamide) (VP-co-DMAm) were prepared by the solvent method (coevaporates) and melting DIP/VP-co-DMAm (cofused) physical mixtures. Differential scanning calorimetry (DSC), infrared spectroscopy (FTIR), and X-ray diffraction (XRD) were used to elucidate the possible interaction between the NSAID drug and VP-co-DMAm in cofused and coevaporated polymer-drug solid dispersions. The XRD and FTIR studies suggest the presence of physical interactions with formation of a charge transfer complex between DIF and the VP-co-DMAm copolymers as a consequence of the coevaporation or cofusion processes. In solution, dynamic and equilibrium solubility studies were determined to elucidate the mechanism of interaction between DIP and VP-co-DMAm copolymers. Thermodynamics data about the DIP: VP-co-DMAm dissolution process indicate that the coevaporated systems are more stable that the cofused systems. The dissolution of the cofused and coevaporated systems was diffusion controlled and the dissolution kinetics followed the Noyes-Whitney and the Levich equations. Molecular simulations using semiempirical quantum chemical calculations reinforce the experimental results, suggesting that the improvement in the DIF solubility could be attributed to the charge transfer complex formation between the drug and VP-co-DMAm copolymers.